2020
DOI: 10.1371/journal.pone.0234401
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in hamstring muscle damage after a marathon

Abstract: Previous studies suggest that marathon running induces lower extremity muscle damage. This study aimed to examine inter-and intramuscular differences in hamstring muscle damage after a marathon using transverse relaxation time (T 2)-weighted magnetic resonance images (MRI). 20 healthy collegiate marathon runners (15 males) were recruited for this study. T 2-MRI was performed before (PRE) and at 1 (D1), 3 (D3), and 8 days (D8) after marathon, and the T 2 values of each hamstring muscle at the distal, middle, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…For all participants, the mid-point line for the thigh region covered by the scans (from the greater trochanter to the medial condyle of the femur) was first identified and used as the anatomical reference (Higashihara et al, 2020). Four most adjacent slices to the mid-point line (2 above and 2 below) from the T2 sequence and 12 most adjacent slices to the line (6 above and 6 below) from the IVIM sequence were further processed.…”
Section: Image Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For all participants, the mid-point line for the thigh region covered by the scans (from the greater trochanter to the medial condyle of the femur) was first identified and used as the anatomical reference (Higashihara et al, 2020). Four most adjacent slices to the mid-point line (2 above and 2 below) from the T2 sequence and 12 most adjacent slices to the line (6 above and 6 below) from the IVIM sequence were further processed.…”
Section: Image Analysismentioning
confidence: 99%
“…Repeated eccentric contractions associated with running could lead to the accumulation of hamstrings microdamage, which puts hamstrings at risk for strain injury (Fyfe et al, 2013). Interestingly, Higashihara et al (2020) showed that compared to the proximal region, the distal and middle portion of the hamstrings are more vulnerable to marathon-induced injuries. Therefore, post-running recovery methods that are effective in reducing local muscle damage at the middle and distal portion of the hamstrings could be promising remedies to prevent running related hamstrings injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endurance competition such as marathon running is recognized for having a high physical and physiological demand [1]. Marathon running could lead to muscle damage Life 2021, 11, 725 2 of 11 due to the cumulus of the high volume of concentric-eccentric muscle contractions [2]. Moreover, muscle fibers damage may provoke leakage of the muscle proteins into the bloodstream and later to subsequent complications, including but not limited to delayed onset muscle soreness (DOMS), rhabdomyolysis, and acute kidney injury [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Marathon running could lead to muscle damage Life 2021, 11, 725 2 of 11 due to the cumulus of the high volume of concentric-eccentric muscle contractions [2]. Moreover, muscle fibers damage may provoke leakage of the muscle proteins into the bloodstream and later to subsequent complications, including but not limited to delayed onset muscle soreness (DOMS), rhabdomyolysis, and acute kidney injury [2][3][4]. After a marathon, monitoring muscle damage is vital to improve posterior recovery and training schedules and reduce injury risk [5,6].…”
Section: Introductionmentioning
confidence: 99%